Pengaruh Budaya Kerja dan Motivasi terhadap Produktivitas Kerja Pegawai Bank Rakyat Indonesia (BRI) Cabang Donggala - Sujarwadi Sujarwadi; Utari Utari; Abd. Rahman; Firza Umar Salim (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to determine the effect of work culture and motivation on the work productivity of employees at Bank Rakyat Indonesia (BRI) Donggala Branch Office, both simultaneously and partially. The population in this study consisted of 39 employees, all of whom were respondents because the number was relatively small. The results of the analysis show that work culture and motivation significantly influence work productivity, with an F significance value of 0.000 (< 0.05). Partially, work culture has a significant influence on work productivity with a t significance value of 0.036 (< 0.05), as does work motivation with at significance value of 0.009 (< 0.05). Thus, both independent variables, namely work culture and motivation, were statistically proven to have a positive and significant effect on employee productivity. The coefficient of determination value of 72.3% indicates that the variation in employee work productivity can be explained by these two variables. Meanwhile, the remaining 27.7% is influenced by factors outside the scope of this study, such as organizational culture, compensation systems, and other managerial factors. These results emphasize the importance of a positive work culture and strong motivation in enhancing employee performance.